Evaluating the Effectiveness of Tithonia Extract as Supplement to NPK17։17։17 on Growth and Yield of Spinah (Spinacia oleracea) in Hydroponics Systems - Daniel Mulengetsi Mishona (Uganda Christian University, 2025)
This research evaluated Tithonian diversifolia extract effectiveness as additive fertilizer on spinach Spinacia oleracea) growth and yield in hydroponic culture.A completely randomized design (CRD), Used six treatments, control (NPK19) and five treatments of NPK17։17։17 with different concentrations of Tithonian extract 50-250ml per 14l Results showed that 250 ml Tithonian extract T6 significantly outranks aligns with research, with 260 % more fresh weight (274.67g) compared to the control. This excellent performance is compared to reading Jama et al. (2000), whose Tithonian biomass contents are presented as high in nutrients (3.5% N, 0.37% P, 4.1% K). At week three, T6 had larger leaf area (107.83cm²), higher growth (20.71cm) and longer and more leaves (6.87) compared to the control treatments. As Partey et al. (2018) predicted, bioactive substance in Tithonian was likely the cause of heightened growth. The results confirm that Tithonian foliar extract at 250 ml /14l can be utilized for complementing NPK17 fertilizer, provide an eco-friendly option that can help minimize excessive dependence on expensive synthetic fertilizers while confirming Kafle et al.'s (2019) through his finding that combination can perform better than synthetic fertilizer alone. Recommendations for use OF the findings determine that Tithonian foliar extract at 250 ml /14l supplemented NPK17 fertilizer respectively were determined. Keywords: Hydroponics, Tithonian diversifolia,NPK17։17։17, Spinacia oleracea).
Undergraduate research